2015
DOI: 10.1590/0001-3765201520130387
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproduction of the mangrove crab Goniopsis cruentata (Latreille, 1803) (Crustacea: Decapoda: Grapsidae) in southeastern Brazil

Abstract: Goniopsis cruentata is a common semi-terrestrial crab in Brazilian mangroves and an important fishery resource for traditional communities in the northeastern Brazilian coast. Aiming to contribute to the knowledge about the species, this study evaluated the carapace width and weight growth curves, the relative growth of weight versus carapace width, and the temporal variation of gonadosomatic and hepatosomatic indices for the species. A total of 524 crabs were collected in a mangrove area of Ubatuba municipali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
3
1
1
Order By: Relevance
“…However, diverging from the results found in this study, Reis et al (2015) presented results for Goniopsis cruentata in which juvenile specimens showed negative allometry and adults positive allometry for the weight/growth relationship. Individual allometries for different locations observed in these crabs indicate that geographic variation (factors such as temperature) may influence the body size determination of Brachyura such as G. cruentata because, according to Lira et al (2015), local conditions influence variations in their biological characteristics.…”
Section: Linear Morphometrycontrasting
confidence: 99%
See 1 more Smart Citation
“…However, diverging from the results found in this study, Reis et al (2015) presented results for Goniopsis cruentata in which juvenile specimens showed negative allometry and adults positive allometry for the weight/growth relationship. Individual allometries for different locations observed in these crabs indicate that geographic variation (factors such as temperature) may influence the body size determination of Brachyura such as G. cruentata because, according to Lira et al (2015), local conditions influence variations in their biological characteristics.…”
Section: Linear Morphometrycontrasting
confidence: 99%
“…Because of the lack of variation in the cephalothorax region's shape during the ontogenetic trajectory, we can infer that this region suffers a greater influence of sexual aspects, in which more enlarged females have greater reproductive success (the existence of hierarchy, for example). According to Reis et al (2015), G. cruentata has a life history that prioritizes reproduction over survival, and rapid growth provides selective advantages for both sexes, with fast-growing individuals reaching sexual maturity with larger bodies.…”
Section: Geometric Morphometrymentioning
confidence: 99%
“…Notable topics for future studies include identifying characteristics that differentiate among populations in various environments (Nóbrega et al, 2014), determining whether reproduction is continuous or restricted to a time of year; genetic characteristics (Vergamini et al, 2011), maximum size for each sex, sex ratio, the size at which reproduction begins (Castilho et al, 2015), and recruitment and mortality patterns (Taddei et al, 2015). The data obtained in these studies serve as a basis for determining the minimum landing size, known as the size in the closed season, as well as making it possible to evaluate the somatic growth of individuals, all of which is essential information for cultivation and population management projects (Reis et al, 2015). Knowledge about the populations of M. amazonicum in freshwater environments, where it completes its life cycle, remains scarce and fragmented (Anger et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A.3). The nitrogen demand of this species is due to its faster growth rate than that of U. cordatus (e.g., Pinheiro et al, 2005;Reis et al, 2015, Leite et al, 2014, De Lira et al, 2015. In animals, an investment in growth increases the nitrogen demand during foraging (Sterner and Elser, 2002).…”
Section: Discussionmentioning
confidence: 99%